Growth of mature boreal Norway spruce was not affected by elevated [CO2] and/or air temperature unless nutrient availability was improved - Sigurdsson, BD; Medhurst, JL; Wallin, G; Eggertsson, O; Linder, S (2013)
The growth responses of mature Norway spruce (Picea abies (L.) Karst.) trees exposed to elevated [CO 2 ] (C E 670-700ppm) and long-term optimized nutrient availability or elevated air temperature (T E +3.9 °C) were studied in situ in northern Sweden in two 3 year field experiments using 12 whole-tree chambers in ca. 40-year-old forest. The first experiment (Exp. I) studied the interactions between C E and nutrient availability and the second (Exp. II) between C E and T E . It should be noted that only air temperature was elevated in Exp. II, while soil temperature was maintained close to ambient. In Exp. I, C E significantly increased the mean annual height increment, stem volume and biomass increment during the treatment period (25, 28, and 22%, respectively) when nutrients were supplied. There was, however, no significant positive C E effect found at the low natural nutrient availability. In Exp. II, which was conducted at the natural site fertility, neither C E nor T E significantly affected height or stem increment. It is concluded that the low nutrient availability (mainly nitrogen) in the boreal forests is likely to restrict their response to the continuous rise in [CO 2 ] and/or T E .